BATH/ASME 2020 Symposium on Fluid Power and Motion Control 2020
DOI: 10.1115/fpmc2020-2770
|View full text |Cite
|
Sign up to set email alerts
|

Energy Efficient Excavator Hydraulic Systems With Digital Displacement® Pump-Motors and Digital Flow Distribution

Abstract: Environmental and economic factors are driving the development of more fuel efficient off-highway vehicles. The pathway to fuel savings of greater than 50% in an excavator application through utilisation of system architectures unlocked by Digital Displacement technology is presented. Pump flow distribution using digital valves instead of traditional proportional control valves is demonstrated experimentally. The “Workbus” power distribution scheme is demonstrated on a small scale backhoe arm on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Over and above, Pilot valves have more leakage than direct operated valves [143], respond slowly to pressure buildup [144], and are more complex in structure. And as might be expected, Pilot valves tend to have high power losses due to flow passes through bypass orifices [145,146].…”
Section: Generic Difficulties In Pilot Operated Valvesmentioning
confidence: 78%
“…Over and above, Pilot valves have more leakage than direct operated valves [143], respond slowly to pressure buildup [144], and are more complex in structure. And as might be expected, Pilot valves tend to have high power losses due to flow passes through bypass orifices [145,146].…”
Section: Generic Difficulties In Pilot Operated Valvesmentioning
confidence: 78%
“…Jill Macpherson et al carried out a backwardfacing simulation on an 18-ton excavator with the bus system architecture. The energy recycling capacity is raised by the digital displacement pump-motor, and it is confirmed that the simulated fuel saving is 53% to 58% [26]. M. Pellegri et al introduced the multiservice digital displacement pump to the excavator, which allows dynamic distribution of the pump displacement under different pressure levels.…”
Section: Introductionmentioning
confidence: 89%
“…The possible displacement unit sizes are investigated based on the specification in Section 4.1, with offset in the static flow continuities. Considering the example with the VDN-PP topology depicted in Figure 9B with 0 ↔ 1 and 0 ↔ 3, the pressure dynamics appear as Equations ( 5) and ( 6): 7) and (8), bearing in mind that A 1 > A 2 , A 3 > A 4 , resulting in the displacement unit sizes in Equation ( 9):…”
Section: Possible Displacement Unit Sizes For Vdn-ppmentioning
confidence: 99%
“…The field of digital hydraulics has mainly evolved via two paths being digital flow control units and digital displacement units. In both cases, the switching valves and their control play a crucial role for system performance and efficiency [1][2][3][4][5]; however, the energy saving perspectives of digital hydraulics are indeed present and potential application areas broad [6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%